Effectiveness of interpretive exhibits in influencing students’ intention in birdwatching activity at a Bird Interpretive Center, Fraser’s Hill, Pahang, Malaysia - Mokhli, Nuraain Amalina (2022)
Birdwatching has a significant contribution to the sustainability of wildlife and natural resources. In efforts to promote such activity, managers are encouraged to employ non-personal interpretation as an alternative to influence participants’ affect and intention to participate in such activity. Bird Interpretive Centre, Fraser’s Hill, operates to provide educational information on birds and birdwatching activity. However, the exhibits at the centre lacked the interpretive elements and the behavioural objective or the ‘call for action’ that could convey important messages to visitors and influence their affect and behavioural intention. Thus, it hampered the opportunity for the management to promote birdwatching activity through the available exhibits. The present study sought to evaluate the effectiveness of the interpretive exhibit in influencing university students’ intention to participate in birdwatching activity at the Bird Interpretive Center, Fraser’s Hill. The elicitations of students’ salient beliefs and affective responses were used as a basis to design the interpretive exhibit. A quasi-experimental design was utilised using the control and intervention groups to compare the effectiveness of the non-interpretive and interpretive exhibits, respectively. Questionnaire data were collected from 119 first-year students from the Faculty of Forestry and Environment, Universiti Putra Malaysia. The findings indicated significant differences between the mean scores of the control and intervention groups for the affective responses, intentions and design evaluation, except for the birds’ sound construct in the affective responses and the title and contents construct in the design evaluation. The intervention group showed significantly higher mean scores than the control group for all other affective, intention, and design constructs. Besides, a regression test showed a significant association between affect and intention. The intervention group exhibited a more significant predictive value of affect on the intention of ‘plan’ (47.3% of variance explained) and ‘will definitely’ (58.3% of variance explained). However, the control group contributed a higher predictivity of affect on the intention of ‘intend’ (54.7% of variance explained). Results of each affective response construct also showed that students’ affective responses towards birdwatching strongly predicted their intention for all three constructs (intend, plan, will definitely). In contrast, their affective responses towards birds’ special abilities showed the weakest relation with the intention constructs of plan and “will definitely” and no significant association with the ‘intend’ construct. The study has shown that the new interpretive intervention exhibit is more effective in influencing students’ affect and intention to participate in birdwatching compared to the existing non-interpretive exhibit at the Bird Interpretive Centre. These findings indicated that the interpretive exhibit developed in this study successfully delivers the messages and the ‘call for action’ and shapes students’ affect and intention based on the objective of the interpretive exhibit.